2021
DOI: 10.4097/kja.20519
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic effects of norepinephrine versus phenylephrine infusion for prophylaxis against spinal anesthesia-induced hypotension in the elderly population undergoing hip fracture surgery: a randomized controlled trial

Abstract: Background: Elderly population are at increased risk of spinal anesthesia-induced hypotension increasing their risk for postoperative morbidity and mortality. This study aimed to compare the hemodynamic effects of prophylactic infusion of norepinephrine (NE) versus phenylephrine (PE) in elderly patients undergoing hip fracture surgery under spinal anesthesia. Methods: Elderly patients scheduled for hip fracture surgery were randomized to receive either NE infusion (8 µg/min) (NE group, n = 31) or PE infusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…It was found that pre-hydration alone would not eliminate spinal hypotension [ 23 , 24 ]. Therefore, there is increased interest in the use of vasopressors, preferably prophylactic, to decrease the incidence and severity of hypotension [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that pre-hydration alone would not eliminate spinal hypotension [ 23 , 24 ]. Therefore, there is increased interest in the use of vasopressors, preferably prophylactic, to decrease the incidence and severity of hypotension [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that if the occurrence of cerebrovascular accidents was regarded as the only dependent variate and factors such as general anesthesia and number of anesthetic drugs were regarded as the independent variate, then BMI ≥23 kg/m 2 , number of anesthetic drugs ≥4, and intraoperative blood pressure ≥140 mmHg were also the risk factors affecting cerebrovascular accidents in hip fracture patients [ 24 ]. The association of BMI with cerebrovascular accidents lies in the fact that the diet of obese patients has an excessive amount of oil-containing components and that their obesity is aggravated by postoperative bed rest, but when general anesthesia is considered as a variate, body mass can also affect the amount of anesthetic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, norepinephrine has been described as an effective alternative to phenylephrine for the prevention and treatment of hypotension during SA for cesarean delivery 6 11 . Relatively few studies have evaluated the effectiveness of continuous infusion of norepinephrine in preventing IOH in older patients 12 , 13 . Therefore, in this study, we aimed to investigate whether norepinephrine administration can effectively prevent hypotension in older patients aged ≥ 70 years undergoing unilateral primary hip surgery under SA with propofol sedation.…”
Section: Introductionmentioning
confidence: 99%